Preoperative findings predict difficulty during cholecystectomy - Sharma, N.K.; Barolia, D.K.; Sukhadia, M (International Journal of Medical Research and Review, 2015)
Background: Most previous studies evaluating predictive factors for conversion from laparoscopic to open cholecystectomy have drawn conflicting conclusions. We evaluated objective preoperative variables to predict difficulty during cholecystectomy. Methods: This prospective clinical trial conducted in patients undergoing cholecystectomy by open or laparoscopic method in a single surgical unit of M.B. Govt. Hospital, Udaipur between March, 2014 and November, 2014. Abdominal ultrasonography performed in 48 patients before cholecystectomy. The surgeon re-verified sonography findings in the operating room. Many characteristics were subjected to analysis to identify parameters that independently predict difficulty during cholecystectomy. Results: Out of 48 patients with cholelithiasis on sonography, we encountered straightforward normal cholecystectomy in 26 patients (54.16%) and difficult cholecystectomy in 22 patients (45.83%). Laparoscopic cholecystectomy was performed on 22 patients. Analysis demonstrated elevated WBC, low serum albumin, increased total bilirubin, and ultra-sound finding of pericholecystic fluid were independent predictors of difficult cholecystectomy. All 4 factors were more frequently identified in patients who had a diagnosis of acute cholecystitis. Factors evaluated but not found to be significant on analysis included male gender and the presence of diabetes mellitus. Conclusion: These results demonstrate that difficulty during cholecystectomy can be predicted based on parameters available preoperatively. Difficulty during cholecystectomy is more likely in patients who have acute cholecystitis. However, the correlation between its clinical and pathologic diagnosis is poor. Improvements in the ability to determine the difficulty during cholecystectomy have important implications for surgical care.